STUDY ON GEOMETRICAL STRUCTURES AND ABSORPTION SPECTRA OF M\(_4\)\(^{2+}\) CLUSTERS (M = Cu, Ag, Au) ENCAPSULATED IN SAPO-42 ZEOLITE \(β\)-CAGE USING DENSITY FUNCTIONAL THEORY - Thi Thuy Duong, Nguyen; Tuan Cuong, Ngo (HNUE Journal of Science: Journal of Natural Sciences, 2024)
The most stable structures of tetrahedral M42+ cluster (M = Cu, Ag, Au) encapsulated in SAPO-42 zeolite \(β\)-cage have been determined by the DFT method using a/the B3LYP functional and LANL2DZ basis set. Electronic energies, zero point correction to energies and geometries, as well as the charge of the clusters, have been derived accordingly. The results showed that while the Cu-Cu bond length increases much when Cu42+ is in the framework, the Ag-Ag and Au-Au distances do not. The UV-Vis spectra of the [M4@SAPO-42]2+ clusters, which were calculated at the same hybrid B3LYP functional and the LANL2DZ basis set, show strong absorption peaks at 259 nm, 270 nm, and 259 nm for M being Cu, Ag, and Au, respectively. The nature of electronic transitions that are responsible for the absorption peaks in the UV-Vis spectrum of the [M4-SAPO-42]2+ clusters has been revealed.